LEVEL OF STRESS-RESISTANCE OF PERSONALITY AS A DETERMINANT OF TIME PERCEPTION - Naghdalyan , M.K. (Modern Psychology, 2020)
The purpose of this work is studying the relationship between the level of stress-resistance of a person and his perception of time. This was done by methods that measure the perception of a specific period of time and the level of stress resistance.  The study showed that the individual level of stress-tolerance correlates with the perception of time, and the higher the level, the less the perception of time changes after the influence of stressors.
Keywords: perception of time; stress; stress-resistance; stress factors